Empowering PokTan ViCi 10 farmers in Ciomas Rahayu Village through hydroponic and aquaponic cultivation systems - Karmawan, Listya Utami; Hutagalung, Rory Anthony; Yanti; Suryaatmadja, Irwin; Hardjawidjaja, Michelle Nadine; Wulandari, Yasinta Ratna Esti (Journal of Saintech Transfer, 2025)
The Villa Ciomas RW 10 Farmer Group (PokTan Vici 10), actively engaged in urban farming in Ciomas Rahayu Village, Bogor, West Java, has been utilizing a small plot of land located next to the Cisindangbarang River. Their urban farming area already includes a small fishpond but lacks aquaponics equipment. The community service team aims to enhance the utility of the urban farming facilities by installing aquaponics equipment, providing workshops on basic hydroponics and aquaponics knowledge, exploring its business potential, and offering hands-on hydroponics and aquaponics cultivation practice. Throughout the program, the team also conducts monitoring and guidance to ensure successful implementation and address any challenges encountered during the training program. The hydroponic/aquaponics equipment installation was successful; however, nutrient supply from the fishponds only was initially suboptimal, prompting the addition of hydroponic nutrients. Hydroponic techniques were also introduced for vegetable cultivation. Based on a questionnaire analysis conducted before and after the training, the program positively impacted participants, significantly enhancing their knowledge and aquaponic skills (Wilcoxon signed-rank test, p<0.05). In conclusion, the aquaponics equipment was successfully installed, and participants gained foundational knowledge and skills in aquaponics, enabling them to independently manage aquaponics systems through to harvest. Looking ahead, the community members plan to explore business opportunities in selling hydroponics/aquaponics products.